Simulasi Efek Galvanik pada Baja Karbon Sedang Hasil Perlakuan Panas Menggunakan Boundary Element Method (BEM)-3D - Illiyinal Muttaqin; Syarizal Fonna; Syifaul Huzni (Jurnal Teknik Mesin Unsyiah, 2019)
This research simulates the galvanic effect on medium carbon steel from the result of heat treatment using the Boundary Element Method (BEM) -3D. BEM was developed with the assumption that the electrolyte surrounding the anode-cathode system no ions in or out, so that it can be modeled as Laplace domain. The potential value and the current density across the surface of the domain can be determined by solving the Laplace equation using the BEM. The Galvanic effects can be analyzed by using the potential data. To simulate the galvanic effect on medium carbon steel the result of heat treatment, two anode-cathode combination was set. The first combination is the annealing steel as the anode and the normalizing steel as the cathode. While the second combination is a hardening steel as the anode and the normalizing steel as the cathode. The conductivity value of the electrolyte for the galvanic effect simulation is 0.0541 Ω / m. The simulation results of the first combination showed the most negative anode potential value is -104.09 mV and the cathode potential value of -85.41 mV. While the simulation results from the second combination provides the most negative anode potential value are -220.27 mV and the cathode potential value are -85.41 mV. From the simulation can be seen that the potential difference between the first anode-cathode combinations are +18.69 mV and the second combination are +134.86. Thus, the simulation results show that the combination of annealing steel and normalizing steel produce galvanic effect is relatively small. While the combination of hardening steel and normalizing steel provide galvanic effect is relatively large.